THE ROLE AND CONTRIBUTION OF THE AGRICULTURAL SECTOR IN BENGKULU PROVINCE 2011-2023 (LQ and DLQ Analysis) - Revolina, Ellya; Dwiarsyah, Teguh (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
The Development of the agricultural sector plays an important role in Indonesia. The majority of Indonesia's population depends on the agricultural sector for their livelihoods. The amount of Gross Regional Domestic Product in the agricultural sector which is increasing every year will have a positive impact on Indonesia and the regions which are currently undertaking the process of regional development in a better direction. This research aims to determine the role and contribution of the agricultural sector in Bengkulu Province in 2011-2023. The role of the agricultural sector is categorized into basic or non-basic. This type of research is quantitative sourced from secondary data, namely Gross Regional Domestic Product (GRDP) at the Bengkulu Province Central Statistics Agency. The analysis used is using Location Quotient (LQ) analysis to determine basic and non-basic sectors, Dynamic Location Quotient (DLQ) to see the role of the agricultural sector in the future, Shift Share to see shifts in the agricultural sector and Overlay to see comparisons of LQ analysis, DLQ and Shift Share.LQ in the agricultural sector is 1.32, indicating that the agricultural sector in Bengkulu Province is the economic base score. The DLQ value shows 1.64, meaning that the agricultural sector will remain the base sector in the future. The results of the Shift Share proportional shift (Mij) analysis of 3,910.41 million rupiah indicate that the growth rate of the agricultural sector in Bengkulu Province has increased. Meanwhile, the results of the overlay analysis of the agricultural sector include the classification of positive contribution and positive growth. This means that the agricultural sector in Bengkulu Province during the period 2011-2023 is superior in terms of both contribution and growth